Implementation of Guided Discovery Learning Model Assisted by Google Sheets to Analyze Interest and Learning Outcomes of Class XI Students on Basic Law of Chemistry - -, Thomas Calvin; Sri Susilogati Sumarti (Chemistry in Education, 2024)
Various studies have shown that applying the guided discovery learning model can increase students' interest in learning, which ultimately leads to better learning outcomes. This is especially important for difficult subjects or topics, such as basic chemistry laws. Based on observations at SMA Kristen YSKI, the researcher found indications of low student interest in chemistry. This study aims to analyze students' learning interest and learning outcomes as well as the relationship between the two. The research, using an explanatory sequential design, was conducted on Grade XI Fearless and Genuine students. Data on learning interest was collected through a psychometric scale questionnaire, while learning outcomes were measured through a test, followed by qualitative data collection through interviews. The data was then analyzed using descriptive statistics and correlation analysis between learning interest and learning outcomes. The results of the study provide data on students' interest in chemistry and their learning outcomes in basic chemistry laws, including distribution and central tendency analysis. Interestingly, some students with high learning interest scored low on the test, which was an unexpected result. Interviews were conducted with these students to understand the reasons behind this outcome. Some of the reasons mentioned included difficulty adjusting after the semester break, a tight schedule of tests and extracurricular activities, and a mismatch with the applied learning model, which led to less effective learning.